Impact of Ethno-Cultural Beliefs On A Person With Mental Illness: A Case Report - Rajbhandari, N; Shakya, DR; Sapkota, N; Basnet, M (Journal of Psychiatrists’ Association of Nepal, 2014)
Culture, though difficult to define, is a collection of beliefs, attitudes, knowledge, customs, habits and behaviour which influence cognitions and social development of a patient. Cultures determine how sickness and illness are defined and that will determine what the first port of call is. It also colors the psychopathology. We here describe a case of a 36 years woman who presented with psychosis which co-occurred with left temporal lobe lesion who had significant delay in receiving proper treatment because of the ethno-cultural beliefs. DOI: http://dx.doi.org/10.3126/jpan.v3i1.11353 J Psychiatrists’ Association of Nepal Vol .3, No.1, 2014: 45-47